Anatomy Discourse Analysis on Images 2024 Presidential Candidate: Dimensions Semiotic of Theo van Leeuwen - Muthmainnah Mursidin; Ida Ilmiah Mursidin (Edumaspul: Jurnal Pendidikan, 2023)
The term ‘discourse’ is often used to denote an extended stretch of connected speech or writing, a ‘text’. ‘Discourse analysis’ then means ‘the analysis of an extended text, or type of text’. This article used Using Anatomy Discourse analysis makes it easier for us to analyze a discourse so that the explanation given is structured and in accordance with its stages. From each stage it directs us to interpret all related matters that are in the object of study both from the evaluation stage: it explains what the actual meaning of the image is that is the object of study, purposes: At this stage the public has assumptions/opinions about Anies Baswedan's achievements while serving as the Governor of Jakarta so that he has a big chance to become a candidate for president of Indonesia, and legitimations: At this stage, there will be positive and negative legitimacy from Anies Baswedan's sympathizers who could become the opposition by looking at some of the previous cases when he served as Governor of Jakarta. The cases will be revealed again so that sympathizers will consider them in the 2024 presidential election, whether to remain loyal sympathizers or not to sympathize anymore.